ANALISIS TEKSTUAL NOVEL THE DEVIL IN THE BLACK JEANS - Yuliatin, Riyana Rizki (LPPM Universitas Bumigora Mataram, 2019)
This study aims to explore the form of The Devil in the Black Jeans by AliaZalea, so Formula Literature used to understand it. Words and events in the novel as main data. The method used by analyzing parts of novel based on typology of formula literature and conecting with other similar fictions. The results show the formula such as: hero describes as a figure who close perfect; heroin describes as a common person; heroin gets gift from hero; love confession; love obstacles; touch of affection; happy ending story. Those formula could be found in romance novels such as Summer in Seoul and Pride and Prajudice. It can be said that The Devil in the Black Jeans is popular novel in romance genre.